TELAAH DIGITAL ENTREPRENEURSHIP: SUATU IMPLIKASI DALAM MENGATASI PERMASALAHAN EKONOMI - Perwita, Dyah (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Digitalization is one of the main factors that is very important in developing creative and innovative entrepreneurship activities, where almost everything in the life sector has gone hand in hand with digitalization. It is important for entrepreneurs to always be up to date on technological developments and business digitization. Considering that the industrial sector which will become a field for entrepreneurs to enter is currently dominated by digital platforms. Without sufficient attention related to this digital era, entrepreneurs of course will not be able to compete and maintain their ideas in the expected industry. Therefore, writing this article aims to discuss in detail everything about digital entrepreneurship using the literature review method so that it is expected to provide studies that are in accordance with actual conditions and circumstances.Keyword: Digital Entrepreneurship, Entrepreneurship